Peranan e-Learning dalam Peningkatan Minat dan Proses Pembelajaran Bahasa Mandarin: Studi Kasus Mahasiswa Sastra China Universitas Bina Nusantara - Henny Lim (Bina Nusantara University, 2007)
Bina Nusantara University is a university with a rapid development of its e-learning system in the teaching-learning process and Chinese Department is one department using the e-learning system. This research was done to find out the role e-learning in improving the students’ interest in studying Chinese language. Data were collected by interviewing lecturers and distributing questionnaires to 120 students. Then, the data were tabulated and analysed. The result of the research shows that the respondents are familiar with Binusmaya – the e-learning system used – but they seldom use it because they do not think of its benefit. Thus, it can be concluded that Binusmaya does not both support the students of the Chinese Department in the teaching and learning process and in improving the students’ interest.